Decline in mortality in patients with dementia: Results from a nationwide cohort of 44 258 patients in the Netherlands during 2000 to 2008. (31st July 2018) - van de Vorst, Irene E.; Vaartjes, Ilonca; Bots, Michiel L.; Koek, Huiberdina L.
Abstract : Objective: To investigate whether mortality and readmission risk have changed over the last decade. Methods: Prospective hospital‐based cohort of 44 258 patients with dementia admitted to hospital or visiting a day clinic between 2000 and 2008. Absolute risks (ARs) of 1‐ and 3‐year mortality and 1‐year hospital readmission were quantified and stratified by type of care (day clinic or inpatient care). Cox models were used to compare hazard ratios (HRs), adjusted for age, sex, comorbidity, of death, and readmission across the years using 2000 as the reference group. Results: One‐year mortality declined among men visiting a day clinic (AR in 2008 versus 2000: 13.0%, 29.9%; HR 0.41, 95% CI, 0.30‐0.55). Among inpatients, these ARs were 48.7%, 53.0% (HR 0.85, 95% CI, 0.77‐0.94). Three‐year mortality also declined (AR for men visiting a day clinic: 37.5%, 58.4%, HR 0.53, 95% CI, 0.43‐0.64; for inpatients: 74.4%, 78.9%, HR 0.80, 95% CI, 0.73‐0.88). Whereas 1‐year readmission risk decreased among men visiting a day clinic (AR 44.1%, 65.9%, HR 0.52, 95% CI, 0.43‐0.63), the risk increased among inpatients (AR 36.9%, 27.6%, HR 1.48, 95% CI, 1.28‐1.72). Conclusion: One‐ and 3‐year mortality remarkably declined. One‐year hospital readmission risk increased among inpatients and decreased among patients visiting a day clinic. The results should raise awareness for the increased survival with dementia, as this has direct consequences for patients and (in)formal caregivers, and probably also for health care costs.